Society 5.0's rise of GenAI and the impact on critical thinking in DE - Suliman, Zuleika (Frontiers in Education, 2026)
This qualitative study investigates the impact of Generative Artificial Intelligence in academia and explores strategies to empower critical thinking within the framework of Society 5.0, a human-centered vision of technological advancement that emphasizes the ethical integration of digital innovation and social wellbeing. As tools such as Gemini, ChatGPT 5.0, and BlackBox become increasingly embedded in research and writing practices, concerns have emerged that over-reliance on these technologies may limit critical analysis and original thought. Based on qualitative data from 16 students and one lecturer at a South African higher education institution, the study examines how GenAI influences critical thinking and cognitive presence in scholarly work. The findings reveal that GenAI can enhance critical thinking, metacognitive awareness, and cognitive presence when used reflectively and within pedagogical guidance. The study recommends the development of critical AI literacy to strengthen cognitive engagement and sustain originality to ensure that human creativity remains central to learning and scholarship in Society 5.0.